Receiving a Diagnosis of Pernicious Anemia: Exploring Experiences of Relationships With Health Professionals. (October 2020) - Seage, Catherine Heidi; Glover, Emily; Mercer, Jenny
Objectives: Pernicious anemia (PA) is a chronic condition caused by vitamin B12 deficiency. This is a qualitative study using interpretative phenomenological analysis (IPA), which aimed to explore the patients lived experience of diagnosis and treatment. Methods: Eleven semistructured interviews were conducted in PA patients; these covered participants' diagnostic and treatment journeys, the responses of others to their diagnosis, and the role health professionals have played in their medical care. Interviews were analyzed for recurrent themes using IPA. Results: Three superordinate themes were identified: "The struggle to achieve a diagnosis, " "The significance of a diagnosis, " and "Battling for sufficient treatment." Participants were dissatisfied with their medical care due to diagnostic delay, insufficient treatment, and poor relationships with their health professionals. Many experienced, anticipated, and internalized stigma, which led to a reduced quality of life and withdrawal from the medical profession. Discussion: Participants' interactions with their health professionals hindered their adaptation to their condition; this affected their psychological and physical well-being. Increased clinician awareness of stigma in the PA population symptoms and effective patient-centered communication is required.